Model Digital Public Relation Community Tourism dalam Pemberdayaan Pariwisata Glamping di Malang Dreamland - Teguh Hidayatul Rachmad; Yohanes Probo Dwi Sasongko (Institut Nurul Islam Mojokerto, 2025)
The presence of digital public relations has a very important role in advancing the economy of a business sector. A significant contribution in implementing digital public relations can be seen from the increasingly widespread and mushrooming use of companies on social media. The Malang Dreamland tourist attraction is one of the tourist attractions that fully utilizes the role of technology by presenting digital public relations community tourism to the community. The orientation that we want to present is the creation of an image and brand that exists in society in a positive way. The digital public relations activities carried out by the Malang Dreamland tourist attraction are also based on developments over time and very complex market needs. So, by building a model for business development in the tourism sector by optimizing the role and existence of digital public relations at the Malang Dreamland tourist attraction, it is hoped that it will be able to continue to develop the market and create awareness among the public and tourists, both nationally and internationally, to develop and increase tourism development. in the country, especially in Malang, East Java.